SIGN SYSTEM RUMAH SAKIT UMUM DAERAH Dr. MUHAMMAD ZEIN PAINAN - FEBRIADI ABRAR, San Ahdi, S.Sn., M.Ds., Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Sign system at the Regional General Hospital Dr. Muhammad Zein Painan not functioning properly because it has not provided the information needed, so that not informative and functional. Size of sign system is too small so that patients and visitors find it difficult to see and read the contents, Placement of sign system that are not right so that the sign system does not appear and becomes malfunctioning. The purpose of the design is so that the sign system designed can be informative and functional. Design methodology in designing a sign system through descriptive qualitative methods with a 5W + 1H analysis approach (what, where, when, who, why, how) that can answer and solve existing problems and develop creative design ideas. Data obtained from direct observation to the main source place and using documentation techniques. The results of the design sign system consists of several main media, namely identification sign, direction sign and mapping who has the main concept of being friendly. Supporting media in designing a sign system consists of ID cards, stickers, stamps, pins, welcome signs, and notebooks.Keywords: Hospital, Sign System